Dignity: a prerequisite for attractive work in elderly care. (28th July 2017) - Keisu, Britt-Inger
ABSTRACT: This article explores discourses of new public management (NPM) and dignity at work by considering how attractive work is represented by managers and professionals in Swedish elderly care. The analysis, guided by critical discursive psychology, uses qualitative interviews with 31 managers, nurses, physiotherapists, and occupational therapists at nine workplaces. Three storylines of how attractive work is represented were identified: salary and status, high-quality care, and working conditions and competence. These storylines revealed two strategies by which dignity is attained and defended: strategies of resistance and strategies of organizational citizenship. A conclusion is that identity, power, and position are key aspects for interpreting how managers and professionals navigate between discourses of dignity. Work in elderly care is under pressure from the major shift towards neoliberalism and the techniques of NPM. Discourses upholding NPM are present to only a limited extent, whilst discourses rejecting NPM principles and safeguarding dignity at work and dignity as care providers constitute the basis of the representations. Hence, another conclusion is that the consequences of NPM undermine prior conceptions of the importance of care work. Although dignity at work appears to be a prerequisite for attractive work, it may be an unattainable goal for organizations.